Stable isotope evidence of juvenile foraging in prehistoric Central California. (June 2016) - Greenwald, Alexandra M.; Eerkens, Jelmer W.; Bartelink, Eric J.
Abstract: Ethnographic evidence demonstrates that hunter–gatherer children may forage effectively enough to supplement an adult provisioned diet, where ecology, subsistence strategies, and social organization are conducive to juvenile participation. We use stable isotope measures (δ 15 N and δ 13 C) from bone collagen and serial-samples of dentinal collagen extracted from first molars to examine childhood dietary patterns among 24 individuals from the Late Holocene Central California site CA-ALA-554. We identify weaning age and early childhood dietary patterns, and find evidence for independent child foraging among 25% of the sample population ( n  = 6), the majority of whom lived during the high-stress Medieval Climatic Anomaly (1100–700 BP). Highlights: A model for the detection of independent child foraging among archaeological populations of hunter-gatherers is proposed. Stable isotope data provide evidence of independent child foraging behavior at a prehistoric Central California site. Rates of independent foraging among children are highest during the high-stress Medieval Climatic Anomaly (1100-700 BP).